STUDY ON ANTI-TUMOR EFFECT OF TOTAL GLYCOSIDES FROM RADIX PAEONIAE RUBRA IN S180 TUMOR-BEARING MICE - Xu, Wanpeng; Zhong, Wei; Liu, Jinlan; Liu, Hong; Zhu, Bing (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the paper was to study the anti-tumor effect of total glycosides from Radix paeoniae rubra in S180 tumor-bearing mice, and to preliminarily explore its mechanism of action. Mice were made into S180 solid tumor model, grouped and administered with the extracts; tumor inhibition rate was measured by harvesting the tumors, and serum IL-2 and IL-4 levels were measured by taking blood samples. Total glycosides of Radix paeoniae rubra significantly inhibited the growth of tumor cells in tumor-bearing organisms, enhanced the cytotoxic activity of NK cells, and increased the serum IL-2 and IL-4 levels. Total glycosides of Radix paeoniae rubra have some anti-tumor effect in vivo, which might have been accomplished through the regulation of the immune system.